Revenge Fantasies After Experiencing Traumatic Events: Sex Differences - Goldner, Limor; Lev-Wiesel, Rachel; Simon, Guy (Frontiers in Psychology, 2019)
Experiences of humiliation, unjust hurt caused by another or anger naturally elicit the desire to seek revenge and fantasies of revenge. The current study examined the associations between a history of traumatic events and feelings of injustice and levels of desire for revenge-seeking and fantasies of revenge. Specifically, it tested whether feelings of injustice mediated the associations between the number of past traumatic events and the desire for revenge or revenge fantasies. Based on recent studies showing that retaliatory violence is gendered, sex differences in levels of feelings of injustice, desire for revenge and the presence of revenge fantasies were explored, as well whether participants' sex conditioned the mediation models. The results showed positive associations between feelings of injustice and the desire for revenge and revenge fantasies. The mediation model indicated that feelings of injustice mediated the associations between the number of previous traumatic events and the desire for revenge or revenge fantasies. Men had higher levels of revenge fantasies than women, whereas women tended to perceive revenge as pointless. A sex effect was found for the mediation model, which revealed significant regressed models for women but not for men. The clinical implications are discussed. Keywords: desire for revenge, fantasies of revenge, sex differences, trauma history